The implementation of brand management in the activity of “Рoletehnika” - Hurzhii, Natalia; Fukleva, Yulia (Management and Entrepreneurship: Trends of Development, 2019)
Purpose. The paper purpose is to study the formation of the brand and its implementation in the organization`s work.Design/methodology/approach. The basic principles of the research are systematic, comparative methods, the analysis of literary sources have been used.Findings. The purpose of the research is to consider the process of creating brand and its formation as an integral part of the social, cultural aspects of consumer life, as well as its implementation into the work of the enterprise. The relevance of the topic is determined by the transformation of marketing and advertising activities, due to various structural reorganizations at the enterprises, crises and political situations, where the formation and implementation of the brand plays a leading role. Moreover, not every process can be named as developing and managing a brand, but that, where the product becomes the most valuable, recognizable and preferred for consumers.Research limitations/implications. The scientific significance of the work lies in a detailed study of the development and management of the brand on the example of a particular enterprise and the understanding that it is of great value to consumers. Moreover, our research in the field of brand management will help future young scientists to understand better the problems of brand formation and its development in companies.Originality/value. Such knowledge will help to increase the competitiveness of the Ukrainian economy and accelerate the process of integrating the country into the world economy. Further research on the development of brand and its implementation can help to develop the management in a numerous organizations, increase output and the products can break into market in a short time.